Note on Strains of the Cabbage Maggot, Hylemya brassicae (Bouché), (Diptera: Anthomyiidae), Resistant to the Chlorinated Hydrocarbon Insecticides in Western Newfoundland - Morris, Ray F. (The Canadian Entomologist, 1963)
In October, 1960, growers in the Robinsons-St. Davids area of Newfoundland reported that aldrin and heptachlor no longer protected rutabagas and cabbage adequately from attack by the cabbage maggot, Hylemya brassicae (Bouché). In 1961, an experiment was conducted in the area, at Jeffreys, to determine if strains resistant to chlorinated hydrocarbons had developed. Six plots, each containing 58 cabbage plants, were set up on June 13 in an area heavily infested with the maggot in the previous years. The insecticides, rates of application, and results obtained are shown in Table I. All treatments were applied two days after transplanting and concentrated in the soil around the stems of the plants.